Pooled safety analysis of two phase 3 studies investigating trifluridine/tipiracil plus bevacizumab in patients with metastatic colorectal cancer - Taieb, Julien; Fakih, Marwan; Liposits, Gabor; Prager, Gerald W.; Van Cutsem, Eric; Ciardiello, Fortunato; Amellal, Nadia; Calleja, Elizabeth; Liu, Mei; Roby, Lucas; Tabernero, Josep; André, Thierry (Frontiers in Oncology, 2025)
BackgroundTrifluridine/tipiracil (FTD/TPI) is approved as monotherapy and in combination with bevacizumab for the treatment of patients with refractory metastatic colorectal cancer (mCRC). FTD/TPI plus bevacizumab showed good tolerability in the phase 3 SOLSTICE (first-line) and SUNLIGHT (later-line) trials. This pooled analysis was performed to further characterize the safety of FTD/TPI plus bevacizumab and to compare safety in untreated and previously treated patients with mCRC.MethodsPatients must have received at least one dose of FTD/TPI plus bevacizumab in SOLSTICE (NCT03869892) or SUNLIGHT (NCT04737187). Treatment-emergent adverse events (TEAEs) in SOLSTICE and SUNLIGHT were graded per Common Terminology Criteria for Adverse Events versions 4.03 and 5.0, respectively. Times to onset/resolution of grade ≥3 hematologic TEAEs were assessed using Kaplan–Meier methodology. Treatment-related adverse events (TRAEs) were analyzed by age and Eastern Cooperative Oncology Group performance status (ECOG PS).ResultsThe pooled safety population comprised 669 patients (SOLSTICE, n = 423; and SUNLIGHT, n = 246). Grade ≥3 TEAEs were reported more frequently in SOLSTICE than in SUNLIGHT (86.8% vs. 72.4%), the most common being neutropenia and anemia. Overall, granulocyte colony-stimulating factor was used in 30.6% of patients. Median time to resolution of grade ≥3 hematologic adverse events/neutropenia to grade ≤2 was 8 days. Grade ≥3 TRAEs were more frequent in patients aged ≥75 years and those with an ECOG PS of 0 versus 1 or 2.ConclusionsFTD/TPI plus bevacizumab showed a consistent and manageable safety profile across first- and later-line mCRC treatment, including in vulnerable patients. Hematologic TEAEs were mostly reversible with appropriate management.